Issues safety and security affecting toward destination image - Siti Nor Suhailah Othman; Siti Nor Hidayah Nor Mohamod; Norain Md Yaman; Yeoh Sin Chia (2016)
In this globalization, safety and security are major concerns for citizens. Safety and security represent many things such as crime, terrorism, natural disaster and others. It is the priority for the tourist or traveler when they are on a trip or vacation. Besides that, the result of this research could be identifying which is the most important issues safety and security that affecting toward destination image and provide the knowledge for the tourists or traveler. There are consists of three issues safety and security which are crime, natural disaster and terrorism. 384 domestic visitors become the respondents. Data was analyzed by using reliability analysis, descriptive analysis and Pearson's Correlation. In the conclusion, crime issue is the highest impact affecting toward destination image rather than natural disaster and terrorism. This finding will help the tourist to know more about the current issues and level of safety in a destination.